PEMBINAAN CARA PENGGUNAAN MEDIA PEMBELAJARAN BAGI GURU MADRASAH IBTIDAIYAH (MI) DARUL JIHAD SANA LAOK PAMEKASAN - Abd Gaffar; Ali Ridho (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAI Al-Khiarat Pamekasan, 2021)
Human resource professionalism is understood as a fundamental mindset for continuously improving competence through learning efforts in response to the changing demands of the times. In order for the basic direction of competency development towards individual professionalism to be clear, competency standards are needed as a measure of competency achievement. From here, it becomes apparent that competency certification, as a written recognition of an individual's competency, plays a very strategic role in facing the complexity of rapid change in this era of globalization. Therefore, a series of educational and training efforts leading to certification must be carried out in an integrated manner by all relevant parties. The result of this dedication is that the mentoring program can be well-organized and run smoothly according to the planned activities, even though not all participants have a good grasp of the material presented. This activity has received a very good response, as evidenced by the participants' enthusiasm in attending the mentoring without leaving before the end of the training time.